What counts as "responding"? Contingency on previous speaker contribution as a feature of interactional competence. (July 2018) - Lam, Daniel M. K.
The ability to interact with others has gained recognition as part of the L2 speaking construct in the assessment literature and in high- and low-stakes speaking assessments. This paper first presents a review of the literature on interactional competence (IC) in L2 learning and assessment. It then discusses a particular feature – producing responses contingent on previous speakers' contributions – that emerged as a de facto construct feature of IC, oriented to both candidates and examiners within the school-based group speaking assessment in the Hong Kong Diploma of Secondary Education (HKDSE) English Language Examination. Previous studies have, similarly, argued for the importance of responding to or linking one's own talk to previous speakers' contributions as a way of demonstrating comprehension of co-participants' talk. However, what counts as such a response has yet to be explored systematically. This paper presents a conversation analytic study of the candidate discourse in the assessed group interactions, identifying three conversational actions through which student-candidates construct contingent responses to co-participants. The thick description about the nature of contingent responses lays the groundwork for further empirical investigations on the relevance of this IC feature and its proficiency implications.